Evaluation of productivity in tilapia farming for the years 2018 and 2019 using the Malmquist index - Sabbag, Omar Jorge [UNESP]; Bertolini, Renata Melon Barroso (My University, 2022)
Brazilian production stands out among the main tilapia producers and changes in fish systems can lead to increased productivity. Thus, this study aimed to evaluate the productivity indexes in intensive tilapiculture in net-tanks, seeking to investigate the variables that affect efficiency in the months of cultivation for the period 2018-2019, in a case study. Methodologically, the Data Envelopment Analysis technique (DEA analysis) was applied in conjunction with the Malmquist index, in order to calculate the growth of the total factor productivity (PTF) and its components. It was observed that although the productive performance was reduced by 6.7%, a 21.5% increase in technological change (tech) contributed to a 13.4% higher result for the total productivity factor (tfpch) in the period, inferring what technological change was the most important contributor to the growth of PTF. It is concluded that the improvement in productivity should, therefore, focus on managerial skills, in addition to innovation, regardless of seasonality between the months of cultivation, emphasizing that DEA analysis and the Malmquist index are important tools for targeting and decision-making process to those who produce.
Keywords: DEA Analysis; Malmquist Index; Production Evaluation